Optimal patent duration in a lab equipment model - Azevedo, Igor Ribeiro (2019)
In this article we study optimal patent duration in a lab-equipment horizontal innovation growth framework in which patented intermediate goods are imitated - and intellectual property rights (IPR) are as a result overruled. Given a tuple of parameters faced by the policymaker, it may be optimal to choose patent duration so that no R\\&D takes place, to the detriment of BGP trajectories, in contrast to the view that in such a framework reducing patent protection constitutes a social loss. Moreover, as we allow for higher values of the relative risk aversion coefficient, we might find interior solutions to the optimal patent duration problem corresponding to utility models - a type of IPR designed for protecting intermediate goods - terms in OECD countries.